Chronic pain and central sensitization in immuno-inflammatory rheumatic diseases: pathogenesis, clinical manifestations, the possibility of using targeted disease modifying antirheumatic drugs - A. E. Karateev; E. L. Nasonov (Научно-практическая ревматология)
Chronic pain is one of the main manifestations of immuno-inflammatory rheumatic diseases (IIRD), such as rheumatoid arthritis (RA) and psoriatic arthritis (PsA), which determines the severity of suffering, reduced quality of life and disability of patients. Unfortunately, the use of synthetic and biological disease modifying antirheumatic drugs, as well as non-steroidal anti-inflammatory drugs does not always provide sufficient control of pain in IIRD, even when it is possible to achieve a significant reduction in inflammatory activity. The reason for this is the complex mechanism of chronic pain. It includes not onlystimulation of pain receptors caused by damage of the elements of the musculoskeletal system, but also a change in the perception of pain associated with the phenomenon of central sensitization (CS). CS is characterized by a significant and persistent increase in the sensitivity of nociceptive neurons to pain and nonpain stimuli. One of the main theories of the CS development consider this phenomenon as an inflammatory reaction of the neuronenvironmentthe activation of astrocytes and microglial cells, local hyperproduction of cytokines, inflammatory mediators and neurotrophic factors. Factors contributing to the development of CS in IIRD are obesity, depression and anxiety, damage of the somatosensory system, insufficient relief of pain in the onset of the disease. Clinical manifestations of CS in IIRD is hyperalgesia, allodinia, «expanded pain» and secondary fibromyalgia. An important role in the development of chronic pain and CS plays the intracellular inflammatory pathway JAK-STAT. Therefore, JAK inhibitors, such as tofacitinib, used in RA and PsA, can also be considered as an effective means of controlling chronic pain in these diseases.